2018
DOI: 10.1186/s12906-018-2090-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of Chinese herbal injections for treating chronic heart failure: a network meta-analysis

Abstract: BackgroundOn account of deterioration of chronic heart failure (CHF) and extensive exploration of Chinese herbal injections (CHIs), we performed a network meta-analysis to investigate the efficacy of CHIs (Huangqi injection, Shenfu injection, Shengmai injection, Shenmai injection, Shenqi Fuzheng injection, Yiqifumai injection) on the basis of western medicine (WM) treatment in CHF.MethodsLiterature search was conducted in Embase, the Cochrane Library, Pubmed, Chinese Biological Medicine Database, China Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…Considering almost every RCT was conducted on the basis of conventional treatment in both TCM group and control group, it is safe to say that TCM can improve clinical e cacy as complementary to western medicine. The improvement of clinical e cacy was coincided with previous reports [25][26][27][28][29][30] .…”
Section: Discussionsupporting
confidence: 88%
“…Considering almost every RCT was conducted on the basis of conventional treatment in both TCM group and control group, it is safe to say that TCM can improve clinical e cacy as complementary to western medicine. The improvement of clinical e cacy was coincided with previous reports [25][26][27][28][29][30] .…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies reveal that Huangqi can improve cardiovascular function, protect myocardial cells, increase coronary blood flow, enhance myocardial contractility, and have positive inotropic effect on the heart [6,7]. Moreover, Huangqi injection is approved by China Food and Drug Administration and has already achieved positive effect in treating HF in clinical trials [8]. However, the ingredients and targets of Huangqi in the treatment of HF have yet to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Chinese herbal injection (CHI) is a new formulation with rapid action and high bioavailability and made from components extracted from traditional Chinese herb using modern technology . It is widely used in the treatment of cardiovascular diseases, cancers and respiratory diseases . Although numerous traditional pairwise meta‐analytic reviews have reported on the efficacy of many CHIs that could be used to treat mycoplasma pneumonia in children, the effect of which kind of injection is the best remains unclear.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…18 It is widely used in the treatment of cardiovascular diseases, cancers and respiratory diseases. [19][20][21][22][23][24] Although numerous traditional pairwise metaanalytic reviews have reported on the efficacy of many CHIs that could be used to treat mycoplasma pneumonia in children, [25][26][27][28] the effect of which kind of injection is the best remains unclear. This is because the traditional pairwise meta-analysis can only achieve direct comparison between the two interventions and cannot comprehensively evaluate the efficacy of various interventions.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%